Economic Effects of Renewable Energy Expansion: A Model-Based Analysis for Germany - Jur̈gen Blazejczak; Frauke G. Braun; Dietmar Edler; Wolf-Peter Schill (Renewable and Sustainable Energy Reviews, 2014)
The increasing utilization of renewable energy sources (RES) is a major energy policy strategy in many countries worldwide. Germany is a forerunner in the deployment of RES and has ambitious goals for the future. The support and use of renewables affects the economy: It creates business opportunities in sectors producing renewable energy facilities, but comes with costs related to supporting its deployment. This paper analyses and quantifies the net balance of economic effects associated with renewable energy deployment in Germany until 2030. To this end, we use a novel model, the `Sectoral Energy-Economic Econometric Model'. This is an econometric multi-country model which, for Germany, contains a detailed representation of industries, including 14 renewable energy technology sectors. Our results show that renewable energy expansion can be achieved without compromising growth or employment. The analysis reveals a positive net effect on economic growth in Germany. Net employment effects are small, but also positive. Their size depends strongly on labour market conditions and policies. Results at the industry level indicate the size and direction of the need for restructuring across the sectors of the Germany economy.
Additional information: This is the preprint of an article published in Renewable and Sustainable Energy Reviews 40 (2014), pp. 1070-1080, available online at: http://dx.doi.org/10.1016/j.rser.2014.07.134
Keywords: Q43; Q52; C5; 330; Renewable energy; Net economic effects; Germany; Energieversorgung; Erneuerbare Ressourcen; Deutschland